2014
DOI: 10.1155/2014/272961
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Lymphoma: A Single Centre Experience

Abstract: Background. Acute kidney injury (AKI) is a common but least studied complication of lymphoma. Objective. To determine the frequency and predictors of AKI in lymphoma and to study the impact of AKI on hospital stay and mortality. Methods. Retrospective review of medical records of hospitalized lymphoma patients aged ≥14 years between January 2008 and December 2011 was done. Results. Out of 365 patients, AKI was present in 31.8% (116/365). Multivariate logistic regression analysis showed that independent predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…In our study, about one‐third of the patients with cancer experienced an AKI event at least once. As reported in previous studies, hematologic malignancy was the most common type of cancer associated with AKI development (55.4%), which was a similar incidence in our study …”
Section: Discussionsupporting
confidence: 91%
“…In our study, about one‐third of the patients with cancer experienced an AKI event at least once. As reported in previous studies, hematologic malignancy was the most common type of cancer associated with AKI development (55.4%), which was a similar incidence in our study …”
Section: Discussionsupporting
confidence: 91%
“…Acute kidney failure occurs in 12% to 36% of patients with cancer and is accompanied by substantial morbidity and mortality . From 16% to 23% of patients with cancer who are admitted to the ICU develop severe renal failure and require renal replacement therapy .…”
Section: Icu Referral Of Critically Ill Patients With Cancermentioning
confidence: 99%
“…75 Acute kidney failure occurs in 12% to 36% of patients with cancer and is accompanied by substantial morbidity and mortality. [76][77][78] From 16% to 23% of patients with cancer who are admitted to the ICU develop severe renal failure and require renal replacement therapy. 79,80 The etiology of renal failure in patients with cancer is often multifactorial and can be caused by the tumor itself or by drug-related toxicity.…”
Section: Indications For Icu Admission Of Patients With Cancermentioning
confidence: 99%
“…In this nationally representative sample of hospitalizations with TLS, we demonstrate higher mortality, adverse discharge and longer LOS in persons with AKI‐D. Previous analyses studying AKI in TLS have either been single‐center studies, have not captured the national epidemiology or have not delineated the impact of dialysis requirement in AKI . International studies have demonstrated that AKI and dialysis requirement are strong predictors of worse outcome in TLS .…”
Section: Discussionmentioning
confidence: 73%
“…Previous analyses studying AKI in TLS have either been single-center studies, have not captured the national epidemiology or have not delineated the impact of dialysis requirement in AKI. 3,7 International studies have demonstrated that AKI and dialysis requirement are strong predictors of worse outcome in TLS. 8 However, to the best of our knowledge, this is the first study demonstrating the frequency, associations and impact of AKI-D in the United States with nationally-representative estimates.…”
Section: Discussionmentioning
confidence: 99%